The Influence Of Personality And Motivational Factors On Entrepreneurial Behavior Through Students' Entrepreneurial Intentions - Rima Lestari; Heti Suherti; Bakti Widyaningrum (Cita konsultindo, 2024)
The research problem is related to the low entrepreneurial behavior and intentions of students, which are caused by personality and motivation. This research method uses a survey with an explanatory design. The approach used in this research is quantitative. This research was conducted at the Department of Economic Education class 2018-2021, Teaching and Education Faculty, Siliwangi University, Tasikmalaya City. The total population is 436 students, using a sampling technique, namely probability sampling of the proportionate stratified random sampling type so that the population will be calculated using the slovin formula where the samples are taken namely 209 students. The data collection technique in this study used a questionnaire and the data analysis technique used was path analysis. The results of the study show that personality and motivation on entrepreneurial behavior through entrepreneurial intentions have a positive and significant direct and indirect effect